When Grandpa is Also the CEO--Resolving Differences in Family-Owned Businesses - Jordaan, Barney (World Bank, Washington, DC, 2014)
Some of the same aspects of family-owned businesses that can give them a competitive advantage are also the factors that contribute to the high levels of destructive conflict that often occur in them. For example, close family ties can contribute to strong bonds of trust and cooperation, but they also can add emotional fuel to the fire when conflicts arise. Barney Jordaan argues that the best cure for these conflicts is prevention-through establishing basic family governance structures and, failing that, dispute resolution processes that are sensitive to the distinctive dynamic and singular needs of a family-owned business. Family businesses are notoriously light in their use of bureaucracy. It is one of their appealing characteristics, and an aspect of their speed and flexibility in problem solving. Their informality and intimacy makes elaborate decision-making methods unnecessary. However, it is a common failing of all growing businesses that they do not recognize how growth is changing them. They are like a child who stays in short pants even when they're splitting at the seams.